2016
DOI: 10.18632/oncotarget.9836
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the efficacy of the pretreatment neutrophil-to-lymphocyte ratio as a predictor of prognosis in renal carcinoma patients receiving tyrosine kinase inhibitors

Abstract: The data on the impact of the neutrophil-to-lymphocyte ratio (NLR) in metastatic renal cell carcinoma (mRCC) patients receiving tyrosine kinase inhibitors (TKIs) are inconsistent. We therefore performed a meta-analysis to assess the prognostic value of pretreatment NLR in patients treated with TKIs for mRCC. We searched the Embase, Medline, PubMed, Cochrane and ISI Web of Knowledge to identify clinical studies that had evaluated the association between the pretreatment NLR and prognosis in mRCC patients. Progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The prognostic significance of inflammatory factors such as albumin, CRC, and PLR has been demonstrated in numerous malignancies. The importance of NLR, as a readily accessible and cost-effective prognostic parameter, was also indicated in different types of cancers, including esophageal, colorectal, bladder, gastric, kidney, breast, lung, pancreatic, and gallbladder cancers, glioblastoma, cholangiocarcinoma, hepatocellular carcinoma, as well as in carcinoma of the ampulla of Vater [11][12][13][14][15][16][17][18][19][20][21][22][23]. Other prognostic parameters associated with survival of patients with ampullary carcinoma include T-stage, involvement of lymph nodes, surgical margin positivity, perineural invasion, lymphovascular invasion, ECOG performance score at the time of diagnosis, and tumor differentiation [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of inflammatory factors such as albumin, CRC, and PLR has been demonstrated in numerous malignancies. The importance of NLR, as a readily accessible and cost-effective prognostic parameter, was also indicated in different types of cancers, including esophageal, colorectal, bladder, gastric, kidney, breast, lung, pancreatic, and gallbladder cancers, glioblastoma, cholangiocarcinoma, hepatocellular carcinoma, as well as in carcinoma of the ampulla of Vater [11][12][13][14][15][16][17][18][19][20][21][22][23]. Other prognostic parameters associated with survival of patients with ampullary carcinoma include T-stage, involvement of lymph nodes, surgical margin positivity, perineural invasion, lymphovascular invasion, ECOG performance score at the time of diagnosis, and tumor differentiation [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrates that NLR has prognostic significance in patients with various types of cancers [916]. Recently, several studies assessed the prognostic significance of NLR in patients with cervical cancer [17–25].…”
Section: Introductionmentioning
confidence: 99%
“…NLR has been shown to be associated with the prognosis of several solid malignant tumors . A meta‐analysis of patients with mRCC receiving TKI showed that high pretreatment NLR is associated with a poor prognosis . Several studies showed the impact of NLR for the prediction of survival benefit in patients undergoing CN.…”
Section: Parameters Associated With Inflammationmentioning
confidence: 99%
“…60 A meta-analysis of patients with mRCC receiving TKI showed that high pretreatment NLR is associated with a poor prognosis. 68 Several studies showed the impact of NLR for the prediction of survival benefit in patients undergoing CN. Although OS was significantly better in the NTx group than in the non-NTx group, OS in a subgroup of patients with a high NLR was similar to that in the non-NTx group.…”
Section: Inflammatory Indexes Consisting Of Peripheral Blood Cellsmentioning
confidence: 99%